Environmental impact of potentially toxic elements accumulated in surface sediments of the Erikli Lagoon, Black Sea coast (Türkiye) - Kükrer Serkan; Uludağ Musa; Erginal Gülsen; Erginal Ahmet Evren (Oceanological and Hydrobiological Studies)
This study aims to (a) determine the concentration and distribution of elements in the surface sediments of the Erikli Lagoon, which are under natural and anthropogenic pressure, (b) determine possible effects on the environment using ecological indices, and (c) reveal possible sources. Multiple elements, total organic carbon and chlorophyll degradation products were analyzed in sediment samples. Enrichment factor (EF), contamination factor (CF), and geoaccumulation index (Igeo) were calculated to determine the sources of the elements. Modified hazard quotient (mHQ), ecological contamination index (ECI), contamination severity index (CSI) and potential ecological risk index (PERI) were calculated to determine ecological risks. It was found that Mn, Hg, As, Fe and Cd entering the lake are of anthropogenic origin. These elements pose a low to moderate ecological threat to the lake. Agricultural and domestic discharges and atmospheric deposition are the main sources of these elements. A moderate ecological risk with an average value of 194.89 was determined in the lagoon based on PERI and contamination levels of metals. The elements that pose this risk are Hg and Cd, due to their high toxicity. According to ECI and CSI, the ecological risk is low, with average values of 0.99 and 0.30, respectively.